Design Local E-Commerce Application Oli Gholi Pay for Online Buying and Selling Transactions - Mardiana Mardiana; Andira Sari; Dina Firliana Nurddin (Komunitas Dosen Indonesia, 2026)
The limited digitalization of buying and selling activities remains a significant challenge for micro, small, and medium enterprises (MSMEs), particularly at the local level. Although national e-commerce platforms continue to grow, many local MSMEs still face obstacles related to accessibility, usability, and system relevance to their business context. This condition underscores the need for localized e-commerce solutions designed to support MSME digital transformation. This research aims to design and develop an Android-based e-commerce application for Baubau City, named Oli Gholi Pay. The main objective is to produce an e-commerce application design that is easy to recognize, user-friendly, and relevant for MSME actors, local government stakeholders, and the general public. The study employs a descriptive qualitative approach combined with application Development methods. Data were collected through observations, interviews, and focus group discussions involving MSME actors. The prototype Development method was applied through the following stages: requirement identification, initial prototyping, prototype evaluation, application coding, testing, final evaluation, and implementation. The research scope includes participant recruitment analysis, system requirement analysis, system architecture and interface design, Development, functional testing, and application implementation and maintenance. The study successfully produced a functional design of a local Android-based e-commerce application that supports online transaction processes and aligns with MSME operational needs. The results indicate that Oli Gholi Pay can support MSME digitalization by expanding market access and facilitating secure, sustainable digital transactions, while also serving as a reference model for future local e-commerce application Development.